Specialized fungal parasites and opportunistic fungi in gardens of attine ants - Pagnocca, Fernando C. [UNESP] (2012)
Ants in the tribe Attini (Hymenoptera: Formicidae) comprise about 230 described species that share the same characteristic: all coevolved in an ancient mutualism with basidiomycetous fungi cultivated for food. In this paper we focused on fungi other than the mutualistic cultivar and their roles in the attine ant symbiosis. Specialized fungal parasites in the genus Escovopsis negatively impact the fungus gardens. Many fungal parasites may have small impacts on the ants' fungal colony when the colony is balanced, but then may opportunistically shift to having large impacts if the ants' colony becomes unbalanced. Copyright © 2012 Fernando C. Pagnocca et al.